Comparison of Inactivated and Oral Poliovirus Vaccines - Hüseyin Anıl Korkmaz; Adem Aydın; Belgin Ünal (Güncel Pediatri)
Introduction: The aim of this study was to compare the rates of systemic and fever reactions of inactivated poliovirus vaccine (IPV) and oral poliovirus vaccine (OPV) at 2, 4, 6 and 18 months of age. Materials and Methods: The study population was made up of 1634 infants at 2, 4, 6, and 18 months of age who had received IPV and OPV vaccines between 2003 and 2008. All parents reported systemic and fever adverse events to the investigator. Results: Systemic and fever reactions were more commonly observed in infants received OPV vaccines than those received IPV vaccines (2.33% vs. 1.12% and 5.2% vs. 2.8%; p<0.05). Infants received IPV vaccines at 2 months of age had higher rates of systemic reactions than those received IPV vaccines at 4, 6 and 18 months of age (1.8%, 0.77%, 0.67% and 0.62%, respectively; p<0.05). Infants who received IPV vaccines at 4 and 6 months of age had higher fever reactions than those received IPV vaccines at 2 and 18 months of age (1.64%, 3.81%, 3.52% and 0.62%, respectively; p<0.05). Similarly, infants who received OPV vaccines at 2 and 4 month of age had higher systemic and fever reactions than those at 6 and 18 months of age (systemic reactions were 15%, 11.11%, 0.77% and 0.17%, respectively; fever reactions were 27.1%, 24.6%, 2.7% and 1.02%, respectively; p<0.001). Irritability and fever were the most frequently reported reactions. Conclusions: This study showed that IPV had lower rates of adverse events than OPV and emphasized the importance of vaccine adverse event reporting system (Journal of Current Pediatrics 2013; 11: 1-5)